ELIXIR‐EXCELERATE: establishing Europe's data infrastructure for the life science research of the future. (9th February 2021) - Harrow, Jennifer; Hancock, John; ,; Blomberg, Niklas
Abstract : A new inter‐governmental research infrastructure, ELIXIR, aims to unify bioinformatics resources and life science data across Europe, thereby facilitating their mining and (re‐)use.